Desain S-Box Fleksibel: Regenerasi Konstanta dan Koefisien Fungsi Linier Berbasis CSPRNG Chaos - Bambang Susanto; Alz Danny Wowor; Vania Beatrice Liwandouw (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2019)
The substitution process in block ciphers usually uses static s-boxes, where the value of each s-box entry is always fixed and the functions are one-to-one. Visually, the dataset pattern in the input is also seen in the output. This will make it easier for cryptanalysts to look at patterns and can predict behavior based on the input. This study designs a flexible s-box where each entry contains a linear function, with constants and coefficients generated by CSPRNG chaos from the key input. The strength of a flexible s-box can be seen when changing key inputs (although 1 bit different) will produce different s-boxes. In addition, the same input dataset values will produce different outputs, so flexible s-boxes are one-to-many. Statistical tests show that the average correlation is in a low category. Tests on the cipher block also fulfill the Shannon Principle. The principle of Iterated Cipher with n-round is filled with n > 5 and 46n random numbers. The Avalanche Effect test on the algorithm gives better results than Two fish even though it is still below the DES.